STUDY OF SLOPE STABILITY IN INGGRAMUI VILLAGE, MANOKWARI DISTRICT, WEST PAPUA PROVINCE: STUDI STABILITAS LERENG PADA KAMPUNG INGGRAMUI KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Ido Krostanto; Ricardo O.M. Hutapea (INTAN Jurnal Penelitian Tambang, 2023)
This research was conducted in Inggramui Village, Manokwari Regency, West Papua Province because visually, there were indications of a decline in soil conditions caused by the intensity of rainfall or the water flow on the slope surface. The problem that is the focus of the research is determining the value of the Safety Factor (FK) in the original conditions and building design at the research location. Furthermore, this research aims to compare and recommend safe or stable slope geometry with FK at the research location using Rockscience Slide software version 6.0. The results of the FK value calculation interpretation based on Rockscience Slide Version 6.0 software show that the original slope FK value based on the Fellenius method is 0.939. In contrast, the Bishop method produces a value of 0.999. For the actual slope height with changes in slope, the FK value based on the Fellenius method is 1.266, and the Bishop method produces a value of 1.331. On the other hand, for the original slope with changes in slope height, the FK value based on the Fellenius method is 1.250, and the Bishop method produces a value of 1.275. From the calculation results, the FK value of the design is included in the category of landslides that rarely occur (slopes are relatively stable) compared to the FK value of the hill in its original condition.